Sectoral Okun's Law and Cross-Country Cyclical Differences - Eiji Goto; Constantin Bürgi (Center for Economic Studies and ifo Institute (CESifo), 2020)
We estimate Okun's law, the negative relationship between output and the unemployment rate, at the sector level for the US, the UK, Japan, and Switzerland to test several hypotheses that may explain why the aggregate Okun's coeffcients are different across countries. Specifically, we show that the sectoral composition is not a driver and find that the sectoral coefficients are proportional to the aggregate in all four countries. We also show that the standard deviation of unemployment is the main driver of the cross-country differences. This is consistent with labor market policies being crucial to explain the cross-country cyclical differences in the aggregate Okun's coefficient.
Keywords: E24; E32; 330; Okun's law; cross-country differences; sectors